Prophylactic Versus Therapeutic Mastectomy: A Contemporary Analysis of the ACS-NSQIP Database - Hendrix, Ryan J.; Lee, Connie; Friedrich, Ann-Kristin; Rouanet, Eva; Larkin, Anne C.; LaFemina, Jennifer (Clinical breast cancer, 2019)
The objective of the study was to evaluate the morbidity, mortality, and postoperative outcomes associated with simple or subcutaneous mastectomy in the management of prophylactic versus therapeutic resection. In this study we aimed to assess if simple or subcutaneous mastectomy for prophylaxis affects perioperative outcomes compared with resection performed for biopsy proven malignancy. The American College of Surgeons National Surgical Quality Improvement Program database was queried for subjects who underwent simple or subcutaneous mastectomy between 2007 and 2012. Patient demographic characteristics, comorbid conditions, and postoperative complications were analyzed. Of the 30,803 patients, 30,644 (99.5%) underwent therapeutic mastectomy and 159 (0.5%) underwent prophylactic mastectomy. Subjects who underwent prophylactic surgery were more likely to be younger (45 vs. 58 years; P < .01) and white (134 [84%] vs. 20,647 [67%]; P < .01). Surgery time was significantly greater in the prophylactic group (265 vs. 166 minutes; P < .01). There was no significant difference in mortality between groups. There was a trend toward greater 30-day morbidity (15 [9%] vs. 1835 [6%]; P = .09) and occurrence of deep venous thrombosis (DVT; 2 [1%] vs. 74 [0.2%]; P = .06) in those who underwent prophylactic mastectomy. After age adjustment, the prophylactic group showed a nearly sixfold increase in DVT (odds ratio [OR], 5.77; 95% confidence interval [CI], 1.37-24.22), which persisted when controlling for surgery time (OR, 4.95; 95% CI, 1.18-20.86). Prophylactic simple or subcutaneous mastectomy incurs significant additional 30-day postoperative morbidity related to perioperative DVT. Risk-mitigating strategies should be considered in the perioperative care of this patient population. Rates of prophylactic mastectomy are increasing in the United States and might be elected for prevention in women with a hereditary predisposition to breast cancer. Using the American College of Surgeons National Surgical Quality Improvement Program database to study 30,803 patients, the data show that women who undergo prophylactic, rather than therapeutic, mastectomy, show a 5.8-fold increased risk of deep venous thrombosis.